2020
DOI: 10.1007/s40430-020-2199-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of titanium in aluminium matrix on densification and forming limit of P/M composites during upsetting process

Abstract: The present work investigates the densification and forming limit of sintered porous aluminium-titanium preforms for various relative densities and titanium particles. The compacts of 1 aspect ratio with 2-6% of titanium contents in aluminium matrix for various relative densities were prepared through powder metallurgy route by applying suitable powder forming pressures. A sequence of the cold upsetting test has been carried out using 0.5 MN capacity of hydraulic press machine at 0.1 s −1 strain rate. The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The amount of porosity has increased with the rise in the compositions of Ti contents which could reduce the RD and the flow behaviour of the samples. 34 Therefore, the effective strain of the sample has reduced due to the larger amounts of pores. Hence, the VN in the sample has been increased and the CDP of the material has reduced.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The amount of porosity has increased with the rise in the compositions of Ti contents which could reduce the RD and the flow behaviour of the samples. 34 Therefore, the effective strain of the sample has reduced due to the larger amounts of pores. Hence, the VN in the sample has been increased and the CDP of the material has reduced.…”
Section: Resultsmentioning
confidence: 99%
“…The flow behaviour of the P/M samples is obstructed by the addition of reinforcements in the samples. 31,33,34 Therefore, the failure strain has reduced for more amounts of Ti contents in the workpiece. Also, the amount of porosity has increased with the rise in the compositions of Ti contents which could reduce the densification of the samples.…”
Section: Volume Of Voidmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Many researchers have evaluated the workability of various P/M samples and they found that the workability of the samples relies heavily on the pores present in the workpiece. [16][17][18][19][20][21][22][23][24][25] They observed that the workability is high for samples with fewer pores and the workability is low for samples with more pores. The authors performed the upsetting test on sintered P/M steel samples and investigated the influence of porosity on the microstructure evolution during the process.…”
Section: Introduction and Literature Studymentioning
confidence: 99%